2007
DOI: 10.1002/pds.1431
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the general practice research database to examine selected congenital heart defects: a validation study

Abstract: The GPRD computerized medical records are sufficient to assess VSD, TOF, and COA. This study confirms that maternal free text provides a low yield of limited information pertaining to the infants' defect, while the infant free text may provide an additional information usually obtainable from practitioner questionnaires. The information provided by an infant free text may limit the need for practitioner questionnaire validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 21 publications
4
35
0
1
Order By: Relevance
“…A handful of studies have used free text to verify clinical conditions in combination with codes; a few of them have used free text to identify cases4 5 while the majority have used free text to verify and validate coded information 3 6–9. However, with the exception of the study by Wurst et al ,7 most studies have little or no detail on the process of selection and review of the free text that was used.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies have used free text to verify clinical conditions in combination with codes; a few of them have used free text to identify cases4 5 while the majority have used free text to verify and validate coded information 3 6–9. However, with the exception of the study by Wurst et al ,7 most studies have little or no detail on the process of selection and review of the free text that was used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this review reported high PPVs over 90% for the recording of anorexia, bulimia, 16 cataract, 17 congenital heart defects (including ventricular septal defects, tetralogy of Fallot, and coarctation of the aorta), 18 inflammatory bowel disease, 19 cerebrovascular disease, diabetes, respiratory tract infection, 19 Paget's disease, 20 hip fracture, 21 upper gastrointestinal bleeding, 22 non-affective and non-organic psychosis, 23 venous leg ulcer, 24 and pressure ulcer. 32 and cardiac arrhythmia, 33 were not as accurately recorded, with reported PPVs lower than 80%.…”
Section: Papers Validating a Diagnosis Or Patient Characteristicmentioning
confidence: 99%
“…The benefit of using primary care databases is that they provide prospective and systematic collection of clinically verified data that can be comprehensive for studying a variety of important outcomes. 13 The Canadian Primary Care Sentinel Surveillance Network (CPCSSN) is one example of a primary care database. It is an electronic medical records (EMR)-based information system for chronic disease surveillance that has been functioning since April 2008.…”
mentioning
confidence: 99%